Remarkable Properties of ZnO Heavily Substituted with Nitrogen and Fluorine, ZnO1‐x(N, F)x. Issue 12 (28th June 2013) - Saha, Rana; Revoju, Srikanth; Hegde, Vinay I.; Waghmare, Umesh V.; Sundaresan, A.; Rao, C. N. R.
<x xml:space="preserve">Abstract</x> Two kinds in a box: The electronic and optical properties of ZnO substituted with nitrogen and fluorine are studied both experimentally and theoretically. The presence of fluorine enhances the incorporation of nitrogen in the lattice. Co‐substitution reduces the optical band gap of ZnO significantly and increases the dielectric constant. The long‐wavelength visible absorption of N, F‐ZnO is reflected in its bright orange color (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>